2019
DOI: 10.1371/journal.ppat.1008066
|View full text |Cite
|
Sign up to set email alerts
|

Linking the effects of helminth infection, diet and the gut microbiota with human whole-blood signatures

Abstract: Helminth infection and dietary intake can affect the intestinal microbiota, as well as the immune system. Here we analyzed the relationship between fecal microbiota and blood profiles of indigenous Malaysians, referred to locally as Orang Asli, in comparison to urban participants from the capital city of Malaysia, Kuala Lumpur. We found that helminth infections had a larger effect on gut microbial composition than did dietary intake or blood profiles. Trichuris trichiura infection intensity also had the strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 67 publications
1
27
0
Order By: Relevance
“…However, unlike for the other genera, there were many OTUs for Lachnospiraceae NK4A136 group which followed the same trend over the time period in the control mouse samples (the entire genus and five OTUs in uninfected untreated mice, and six OTUs in uninfected treated mice, although no differences in the human control samples or in the infected untreated mice). The identification of two different Lachnospiraceae members ( Blautia and Lachnospiraceae NK4A136) among just five genera overall that consistently showed a negative association with infection across species highlights the importance of this bacterial family, which has also been observed to have a significant negative association with whipworm infection among humans from Malaysia ( Lee et al., 2019 ) and mice with chronic whipworm infections (represented by the species Roseburia (20-egg infection, C57BL/6 mice, 35 days post-infection) ( Holm et al., 2015 )).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…However, unlike for the other genera, there were many OTUs for Lachnospiraceae NK4A136 group which followed the same trend over the time period in the control mouse samples (the entire genus and five OTUs in uninfected untreated mice, and six OTUs in uninfected treated mice, although no differences in the human control samples or in the infected untreated mice). The identification of two different Lachnospiraceae members ( Blautia and Lachnospiraceae NK4A136) among just five genera overall that consistently showed a negative association with infection across species highlights the importance of this bacterial family, which has also been observed to have a significant negative association with whipworm infection among humans from Malaysia ( Lee et al., 2019 ) and mice with chronic whipworm infections (represented by the species Roseburia (20-egg infection, C57BL/6 mice, 35 days post-infection) ( Holm et al., 2015 )).…”
Section: Resultsmentioning
confidence: 93%
“…There are a limited number of published papers studying human microbiome members associated with whipworm infections and these papers report disparate results. One study from Ecuador failed to identify significant associations between STHs ( T. trichiura and Ascaris lumbricoides ) and the fecal microbiome ( Cooper et al., 2013 ); a study on Malaysian subjects identified several bacterial taxa associated with inflammation ( Ramanan et al., 2016 ), and another study from Malaysia identified microbiome taxa (and blood markers) associated with whipworm infections ( Lee et al., 2019 ). A study from Sri Lanka identified several taxa significantly associated with hookworm, whipworm, or roundworm infection ( Jenkins et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Enteric parasite infections are among the most common causes of diarrhea in humans in 198 the developing world. While bacterial infections and the gut microbiome have been well-199 studied, the impact of enteric eukaryotic parasites on the microbiome is not well understood, 200 with some reports showing altered microbiome composition (14,(34)(35)(36)(37) while others showed 201 either modest or no impact (38,39). Because these studies often rely on experimental 202 infection with one or few parasite species, they provide limited insight into the broader impact 203 of enteric parasites on the gut microbiome.…”
Section: Discussion 197mentioning
confidence: 99%
“…Furthermore, these diet-dependent changes in microbiota composition were observed within a few days [ 28 , 29 ]. Additionally, age [ 30 ], sex [ 31 ], host immune system and genetics [ 32 ], infectious disease [ 33 ], and antibiotic use [ 34 ] can all impact intestinal microbiome composition in a given individual [ 35 ]. Therefore, although the human microbiota can be remarkably stable over time, studies have shown it is also malleable, suggesting it could be a target for therapeutic manipulation.…”
Section: The Crosstalk Between the Intestinal Microbiome And The Hmentioning
confidence: 99%